(untitled) (Archives of Criminology, 1995)
In Poland, the level of social confidence in a profession results mainly from: qualifications necessary for the pursuit of that procession; respect for the values to which the profession is particularly related, which it is to serve and to protect; the social usefulness of that profession; the degree of responsibility involved in the tasks performed; the arduousness of work; the level of material profits derived; the extent of power involved in the profession; tradition; social respect for the institutions in which persons pursuing that profession are employed; those persons’ professional, social and moral attitudes. From a comparative analysis of many research findings it follows that the legal professions rank relatively low in the hierarchy of prestige. Certain changes have been taking place in this respect during the las 50 years; yet the legal profession still enjoys a rather low level of social acceptance which is rather astonishing: a lawyer has all the traits valued by Polish society. In the period of Polish People’s Republic, the relatively low prestige of the legal profession resulted from the then valid doctrine, state policy, the system of administration of justice, and the attitudes and conduct of judges, public prosecutors, and barristers, In Polish People’s Republic, the law was not an independent value. It was to support the “historical process” and serve not justice itself but rather “historical justice”. It became the tool of social engineering which was to create a new society. Statutory law was transformed into a comprehensively_ oriented instrument of political action ‒ a utilitarian means of government. The legislation was to implement a political, social and economic program imposed from above. There was a dramatic drop in the importance of law as the exponent of values. This was due to a loosening of its natural relation to the sense of morality and justice. A number of decrees and statutes were passed, usually according to the valid procedure but lacking inner justness; they were called law but were essentially utterly lawless in many cases. For this reason, the social sense of justness seldom followed from statutory law; instead, it existed outside of the law so to say. The law-citizen relation included pathological elements. Most of the social experiences of contacts with law and its representatives were negative. The law seldom defended the citizen, especially against arbitrary decisions of the authorities; it usually punished him. The regulatory functions of law yielded precedence to its repressive functions. The conception of unity of state pover ruled out all independence of the judiciary in Polish People’s Republic. The courts were subordinated to the executive authority not only in terms of administration but also to a large extent in their jurisdiction. This resulted from the very procedure of appointing and removing judges; the wide discretion to remove judges; the organization of supervision over judicial decisions; the terms of office of the Supreme Court; the practice of guiding principles for the judiciary, issued by the Supreme Court and binding for all courts. Appointment of desired benches and selection of cases, changes of the benches during proceedings, requests for court files during proceedings, summons of judges to one Ministry or another, individual and organized pressure – all of these were by no means exceptional situations in the courts of Polish People’s Republic. Judicial independence ultimately depends on the judge himself. A part of judges compromised on the norms of professional ethics and on common morality. The actual numer of “obedient” judges is difficult to estimate today. Even if they were few, that was certainly enough for the people’s confidence in courts to be shaken. It would be wrong to believe that the above processes, phenomena and facts remained unnoticed by the people. Society were fully aware of the functions assigned to the law and tasks of the institutions of administration of justice. The opinion knew many examples of public prosecutors, judges and barristers departing from the basic norms of the code of professional ethics. The authorities themselves saw to it, publishing resolutions of the Supreme Court and providing extensive coverage of many trials. Thus social attitudes towards the law, institutions of administration of justice and their representatives eroded continuously. Society had no confidence in the effectiveness of recourse to the law in vindication of one’s claims; they fully realized whose interests the public prosecutor’s oflices and courts actually guarded. The prosecutors and judges were perceived chiefly as functionaries of state. Paradoxically, in a totalitarian system where violations of individual rights were a common everyday practice, the lawyer hardly helped the citizens. The social usefulness of the lawyers’ professional roles grew smaller, and so did their prestige. In coming years the prestige of the legal professions will no doubt go up. This will be a result of: a general consolidation of the role of law in the life of state and society; development of a new law-citizen relation; an increased regulatory function of the law; financial promotion of the legal professions; and improved social image of institutions of administration of justice. There is much to indicate that social regard for the legal professions will eventually reach the Western level. The proces of the Polish hierarchy of prestige of individual professions becoming “European” will inevitably result in its losing its former “proletarian” nature; this will be expressed in a drop in social regard for workers. Already going down today is the pristige of miners, and also of teachers. From 1987 till 1993, the proportion of respondents who declared the greatest regard for miners and teachers dropped by 14 and 4 points respectively. Thus the distance between a judge and a miner dropped by 26, and that between a judge and a teacher – by 16 points. The social image of judges and institutions of administration of justice is shaped by the Poles’ twofold experience: the still fresh memory of “the past” and the not yet really known “present day”. The past meant obedient judges; courts as an extension of the arm of power; sentences clashing with the sense of justice etc. The present day means rampant corruption; frustration: inner dysfunction of the system; lack of skill in resolving matters which the people see as self-evident. The public opinion have not yet fully developed a view on judges and the institutions of administration of justice. A half of respondents believe that courts do good service to society, one-fifth think the opposite, and another one-fifth have no standpoint on the matter. Thus actually two parallel images of courts operate in the social consciousness. Groups which perceive the reality through glasses of the past, so to say, seek yesterday in today’s courts. The future-oriented groups, instead, tend to define those institutions in the categories of the still distant tomorrow. For this reason, even a relatively not too controversial decision taken by the judicial authority brings about an avalanche of the gravest accusations, that of attempting to restore the past included. The psychological conflict is hardly to the court’s advantage: an image still lingers in the social subconscious which prevents society from honestly appraising their work. Also political circumstances are not too favorable for institutions of administration of justice. The active involvement of representatives of the law in resolution of disputes which the opinion define as political makes them party to the conflict in the eyes of society. Past experiences have shown how convenient a tool the court can be in political struggle. Also the Government’s activity bears on the social image of administration of justice. For one year now, the most vehemently criticized area of the Government’s work is its policy of “crime control”. It has been called ineffective by a half of society. An average citizen is convinced that the police, prosecutors, and courts are equally responsible for this situation. The condition of courts with which a large portion of society have contacts is hardly helpful in the building of those institutions’ prestige: dilapidated buildings in desperate need of repair; old worn out furniture; small, underqualified and underpaid and thus frustrated office staff. Added to this should be excessive bureaucracy, obscure procedures, distant time limits, high court fees, excessive fees charged by barristers. The courts have already started regaining social trust but the process is bound to be a slow one. Practically each and every slip of the judicial authority, eagerly pointed out by the media, may well reverse the emerging favorable trend in the attitude of public opinion. Social attitudes towards the courts are incomplete and based largely on emotions which is what makes them unstable. The emerging trend can be consolidated by e.g. closer contacts of the judicial community with society, established chiefly through the media. Yet the new image of Polish courts depends first and foremost on the success of the process of building of state ruled by law.